The Effectiveness of Physical Exercise, Prenatal Yoga and Pregnancy Gymnastics in Primigravida on Childbirth Duration - Linda, Irma; Lubis, Rismahara; Siregar, Yusniar (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2017)
One of the physical exercises favored by pregnant women is pregnancy gymnastics. It is a kind of exercise for strengthening and maintaining the elasticity of abdominal wall muscles, ligaments, and basic muscles of pelvis which are related to the process of childbirth. The objective of this research was to find out the effectiveness of physical exercise method between prenatal yoga and pregnancy exercise in primigravida on childbirth duration so that it could provide information which could increase the knowledge of midwives and midwifery students in providing midwifery care for pregnant women in facing the process of childbirth. This quasi experiment study was conducted in July to September 2016. The subjects was 40 pregnant women. The respondents were all primigravida pregnant women of trimester III who had the pregnancy examined in the Practice of Independent Midwife, Medan Johor. T-test was used for statistical analysis. The result of T-test showed that p-value=0.002 which indicated that there was the difference in the effectiveness of physical exercise method between prenatal yoga and pregnancy gymnastics in primigravida on the duration of normal childbirth. Prenatal yoga was more effective than pregnancy gymnastics in shortening the duration of normal childbirth.